Haematological parameters, haemozoin-containing leukocytes in Sudanese children with severe Plasmodium falciparum malaria - Salih, Magdi M; Eltahir, Hatim G; Abdallah, Tajeldin M; Elmahdi, Tariq E; Khamis, Ammar H; Malik, Elfatih E; Adam, Ishag (The Journal of Infection in Developing Countries, 2018)
Introduction: Haemozoin –containing leucocytes (HCL) can be used to predict severe malaria. Methodology: A case –control study was conducted in Singa, Sudan, to investigate the haematological values and HCL in children with severe Plasmodium falciparum malaria. The cases were children with severe P. falciparum malaria (67). The two groups of controls were patients with uncomplicated P. falciparum malaria (63) and healthy children (50). Results: The mean (±SD) age was 5.5 (±3.8) years. In comparison with children with uncomplicated P. falciparum malaria, children with severe P. falciparum malaria had significantly lower haemoglobin and platelet counts, and significantly higher lymphocyte counts, red cell distribution width (RDW), and platelet distribution width (PDW). The rate of haemozoin –containing monocytes (percentage of children positive for this parameter in each group) was 91.0%, 84.6% and 50.0%, P<0.001 in children with severe P. falciparum, uncomplicated P. falciparum malaria and negative controls, respectively. Receiver Operating Characteristic (ROC) curves for blood parameters and HCL were plotted and the areas under the curve (AUC) were calculated for the prediction of severe P. falciparum malaria infection. The ROC curve analysis, showed a fair predictability of malaria for haemoglobin (AUC = 0.74, sensitivity = 76.0% and specificity = 60.3%, cut-off = 9.7g/dl), lymphocytes (AUC = 0.71, sensitivity = 71.3% and specificity = 62.2%, cut-off = 1.95×103/mm3), PDW (AUC = 0.69, sensitivity = 80.1% and specificity = 66.3%, cut-off = 15.34 %) and haemozoin in the monocytes (AUC = 0.68, sensitivity = 68.2% and specificity = 65.2%, cut-off =5.5 %). Conclusion: RDW, PDW and HCL could be used to predict severe malaria in this setting.